Safety and Efficacy of Telavancin at an Outpatient Parenteral Antibiotic Therapy (OPAT) Unit in New York City. (4th October 2017) - Rodriguez, George D; Polo, Lorena; Urban, Carl; Turett, Glenn; Prasad, Nishant; Warren, Nathan; Tsapepas, Demetra; Ghimire, Rabindra; Segal-Maurer, Sorana
Abstract: Background: Telavancin is an intravenous (IV) lipoglycopeptide with concentration-dependent bactericidal activity against a broad spectrum of gram-positive organisms and is approved for the treatment of skin and skin structure infections and nosocomial pneumonia; however, post-marketing data is limited. At a hospital-based Outpatient Parenteral Antibiotic Therapy (OPAT) unit, telavancin is used to treat patients due to its convenient daily dosing, its lack of need for therapeutic drug monitoring and its potent in-vitro gram-positive activity. We sought to evaluate the safety and efficacy of telavancin in the OPAT setting. Methods: We performed a two-year, IRB-approved, retrospective evaluation of all adult patients admitted to the OPAT unit treated with telavancin. Primary outcome was clinical success defined as completion of telavancin and documented clinical resolution. Secondary outcomes included time to initial clinical improvement, 30-day infection related readmission, frequency and time to acute kidney injury (AKI) per RIFLE criteria and incidence of adverse drug reactions (ADRs). Results: A total of 43 patients were evaluated. Median age was 51 years, 56% were male, and 84% were admitted from the hospital. Baseline demographics differed between clinical failure and success in BMI (38.1 vs. 31 P = 0.168), rates of diabetes mellitus (47% vs. 25% P = 0.148) and chronic vascular insufficiency (33% vs. 11% P = 0.104). Clinical success was observed in 28/43 patients (Figure 1). Successfully treated patients were more likely to be treated for abscesses (21% vs. 0% P = 0.076) and dosed using actual body weight (79% vs. 60% P = 0.196). AKI occurred in 4.7% of all patients, at a median of 7 days after starting (Figure 2). ADRs occurred in 9 patients, of whom 7 led to discontinuation (Figure 3). No difference in time to clinical resolution and 30-day infection-related readmission was observed. Conclusion: Our study shows real-life experience with telavancin in an OPAT setting, demonstrating tolerability, efficacy, and potential factors which may predispose one to clinical failure (BMI, vascular insufficiency, and dosing weight). Further investigation is warranted to better individualize patient selection and optimize dosing and management of ADRs. Disclosures: All authors: No reported disclosures.